Agile polymorphic software-defined fog computing platform for mobile wireless controllers and sensors. (19th September 2019) - Gebre-Amlak, Haymanot; Jabbari, Abdoh M.A.; Chen, Yu; Choi, Baek-Young; Huang, Chin-Tser; Song, Sejun
Softwarisation approaches in networks, storage systems, and smart devices aim to optimise costs and processes and bring new infrastructure definitions and functional values. A recent integration of wireless and mobile cyber-physical systems, with dramatically growing smart sensors, enable new types of pervasive smart and mobile urban surveillance infrastructures that open up new opportunities for boosting the accuracy, efficiency, and productivity of uninterrupted target tracking and situational awareness. Wireless sensors provide the tool for communications and security applications. They offer low-power, multi-functioning and computational capabilities. In this paper, we present a design and prototype of an efficient and effective fog system using light-weight agile software-defined control for mobile wireless nodes. Fog computing or edge computing, a recently proposed extension and complement for cloud computing, enables computing at the network edge in a smart device without outsourcing jobs to a remote cloud. We investigate an effective softwarisation approach in the Fog environment for dynamic big data driven, real-time urban surveillance tasks of uninterrupted target tracking. We address key technical challenges of node mobility to improve the system awareness. We built a preliminary proof-of-concept Light-weight controller architecture on both Android-and Linux-based smart devices and tested various collaborative scenarios among the mobile nodes.